VAS DEFERENS CHARACTERISTIC AND RELATED FACTORS TO SPERM COLLECTING BY MICROTESE IN PATIENTS WITH NON OBSTRUCTIVE AZOOSPERMIA (Vietnam Journal of Community Medicine, 2022)
Objectives: To describe the characteristics of the seminiferous tubules and the relationship tosperm collection by micro-TESE (Microdissection testicular sperm extraction - micro TESE)in patients with nonobstructive azoospermia (NOA). Subjects and research methods: 132NOA patients were performed micro TESE at the Military Clinical Embryo Institute - VietnamMilitary Medical University from 5/2017 to 12/2019. Results: Histopathology of 132 NOApatients showed that the rate of hypospermatogenesis (HP), maturation arrest (MA), Sertolicell only syndrome (SCOS) and hyalinization was 8.33%, 20.45%, 59.85%, and 11.36%,respectively. The diameter of the seminiferous tubules in patients with NOA was smallerthan the normal value, in which the fibrous sheath thickness was thicker. The epithelialcells reduced severely. The percentage of patients with sperm collection was 40.15%. Theprobability of finding spermatozoa in patients with normal seminiferous tubule diameter andfibrous sheath thickness was 5.58 times and 6.20 times compared with patients out of thenormal values. The probability of finding spermatozoa in patients with Johnsen score ≥ 8was 6.66 times higher than that in patients with Johnsen score < 8. Conclusion: There was adifference in characteristics of the seminiferous tubules in NOA patients compared with thenormal value. Histopathology is one of the factors predicting the success of the micro TESEmethod. There was a relationship between seminiferous tubule diameter, fibrous sheaththickness and Johnsen score to sperm collection rate in NOA patients.
Keywords: Microsurgical method to collect sperm from testicles; Non-obstruction azoospermia; Sperm collection; testicular histology.